1945
DOI: 10.1242/jeb.22.1-2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Absorption from the Rumen as Exemplified by the Behaviour of Acetic, Propionic and Butyric Acids

Abstract: The following conclusions were reached by placing a solution of sodium acetate, propionate and buty-rate in the rumen of sheep and studying the rate at which these substances are absorbed: (1) When the rumen contents are at pH 7.5, fatty acid anion only is absorbed, i.e. no free fatty acid is absorbed, and the anion is accompanied by a roughly equivalent amount of sodium. The anion is absorbed by passage through water-filled pores, the diameter of which is large compared with retric acid. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1948
1948
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This latter finding is in conflict with the conclusion of Danielli et al (1945). The direct measurement of the absorption of acetic acid from an 'isolated' rumen, carried out at the same time as the indirect measurement employed by these workers, has shown that their procedure may give rise to misleading results.…”
Section: Loss Of Acetic Acid From the 'Isolated' Rumen (1) By Direct ...mentioning
confidence: 89%
See 4 more Smart Citations
“…This latter finding is in conflict with the conclusion of Danielli et al (1945). The direct measurement of the absorption of acetic acid from an 'isolated' rumen, carried out at the same time as the indirect measurement employed by these workers, has shown that their procedure may give rise to misleading results.…”
Section: Loss Of Acetic Acid From the 'Isolated' Rumen (1) By Direct ...mentioning
confidence: 89%
“…This allowed observations to be made on the essentially intact rumen in its physiological state. The procedure first used by Barcroft, McAnally & Phillipson (1944) and adopted by Danielli et al (1945) was, however, repeated in some experiments. In these the rumen and its associated organs were isolated from the rest of the alimentary tract by tying off the abomasum just below the omasum, taking care to exclude the epiploic vessels.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations